Discriminant Analysis of Morphometries of Nemipterus Species - Mohd Said, Mohd Zaki; Mohammad Mohsin, Abu Khair (1992)
MOIphometric measurements of threadfin bream, Nemipterus spp. (NemijJteridae) in Malaysian waters were analysed using linear discriminant analysis in order to identify the homogenous jJopulations. The percentages of cases correctly classified are 52% for N. marginatus, 92% for N. nemurus, 66% for N. nematophorus, 76% for N. tambuloides, and 90% for N. peronii.